ANALISIS TERHADAP KEMAMPUANPEMAHAMAN KONSEP MATEMATIS SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL (SPLDV) - Eline Yanty Putri Nasution (De Fermat : Jurnal Pendidikan Matematika, 2021)
Mathematical concepts are interrelated with each other so that they must be studied coherently and continuously. Therefore, the mathematical conceptual understanding ability is very important for students. The aim of this research is to analyze students’ mathematical conseptual understanding ability in  Two-Variable System of Linear Equations (SPLDV). This research methodology was qualitative with descriptive approach. The population of this research is all of VIII grade students in MTSN 1 Kerinci which VIII B group was choosen as the research sample with snowball samoling technique. The research instruments that used was mathematical conceptual understanding test and interview. According to the mathematical conceptual understanding ability tests results, most of students in VIII B grade MTsN 1 Kerinci have mathematical conceptual understanding ability in medium category. Three students with mathematical conceptual understanding ability in the high, medium and low categories were selected to be interviewed in order to identify the achievement indicators of the mathematical concepts understanding ability. The students with higher mathematical conceptual  understanding ability showed 5 indicators of mathematical conceptual  understanding ability. The students with medium mathematical conceptual  understanding ability showed 3 indicators of mathematical conceptual  understanding ability. The students with lower mathematical conceptual  understanding ability showed 2 indicators of mathematical conceptual  understanding ability.